The basics of information security understanding the fundamentals of InfoSec in theory and practice - Andress, Jason (Syngress, 2011)
Provides you with fundamental knowledge of information security in both theoretical and practical aspects. This title covers the basic knowledge needed to understand the key concepts of confidentiality, integrity, and availability. It dives into practical applications of these ideas in the areas of operational, physical, network, and application.